Evaluation of the relationship between body composition and aerobic fitness in youth soccer players - Ö. Nalbant; K. Özer (Physical Education of Students)
Background and Study Aim: The purpose of the study was to make an evaluation between aerobic fitnes (VO2max) and body composition in youth soccer players. Material and Methods: U19, U17, U16 and U15 age groups participated in the study. Twenty-eight U19 (average age 18,03±0,58), twenty-three U17 (average age 16,72±0,30), twenty-seven U16 (average age 15,79±0,23) and twenty-one U15 (average age 14,67±0,31) totally ninety-nine athletes voluntarily participated in the study. The subjects’ body weight and fat percentage were estimated by bioelectrical impedance. VO2max was determined by YOYO Intermittan Recovery test protocol. Shapiro-wilk test, Independent t test, hierarchical regression and analysis of covariance were used to compare the relationships between aerobic fitness and body composition. Additionally, Pearson correlation coefficients were calculated to examine the relationships between variables. The level of significance for all statistics was set at p<0.05. SPSS 23 software was used to calculate the data. The total value of all estimators is f = 18,001 and p <0.0001. Results : Although all variables were included in the model, the BMI was considered the greatest explanatory factor for fatness. Aerobic endurance was assessed in direct proportion to age, sit and reach test, crunch test, plank, and long jump test. As the distance increased, the% fat ratio decreased (p <0.001), and the fat ratio decreased with the decrease in the T test (p <0.001). Conclusions: In this study, it was determined that body fat ratio determined by BMI, body fat percentage decreased with increasing aerobic endurance, body fat ratio was negatively correlated with aerobic fitness and lean body ratio. It was also determined that aerobic fitness was positively correlated with age, sit and reach, crunch test, plank, standing long jump and T test.